A CROSS-SECTIONAL STUDY ON KNOWLEDGE AND PRACTICE REGARDING MENSTRUAL HYGIENE AMONG FEMALE NURSING STUDENTS IN A TERTIARY CARE HOSPITAL - ALAK KUMAR DAS; JINIA GHOSH (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Menstruation, though a normal physiological process in the females of reproductive age group, is surrounded by various misconceptions and social taboos. Inadequate knowledge and unhygienic menstrual practices can adversely affect female health. Poor menstrual hygiene practice has been negatively associated with infection of the reproductive and genitor-urinary tract, cervical cancer, absenteeism from school, or drop-out, poor academic performance, lower self-esteem, and poor quality of life. We conducted this study to evaluate the knowledge and practices regarding menstruation in female nursing students in a tertiary care hospital. Methods: An observational, cross-sectional, questionnaire-based study was conducted over for three months on female B.Sc nursing students in the first year to the fourth year through face-to-face interview at the department of Pharmacology in a tertiary care hospital. Data regarding socio-demographic profile, knowledge of obstetric and gynaecological factors, perception of menstruation, and hygienic practice of the participants during their menstruation were collected. Results: Responses from 165 participants were analyzed. The mean (± SD) age of the students was 19.64 (± 1.09) years. Most of their parents had education up to a diploma and above (47.27% among mothers and 70.9% among fathers). The majority of the participants used to experience dysmenorrhea (52.72%) and had pre-menarcheal ideas about menstruation (78.18%). Mother was the most common source of information (54.54%) followed by teachers (16.96%) and media (13.33%). The majority knew the source (89.09%) and cause (100%) of menstrual bleeding. A considerable portion (45.45%) thought menstruation as the sign of conception. The majority (96.36%) used commercially made sanitary pads, and used to dispose of the used sanitary pads in the dustbin (98.19%) by wrapping them with paper (98.19%). Conclusion: Present study found an encouraging picture regarding knowledge and hygienic practices during menstruation among the participants. Education about menstrual hygiene needs to be imparted at the grass root level. In this regard Anganwadi and health care workers, teachers and media can play a major role. All mothers need to be taught about the importance of hygienic practices during menstruation, convey correct information to their daughters, and should be encouraged to break the age-old myths and taboos associated with menstruation.